PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN INFORMASI INTELLECTUAL CAPITAL PADA PROSPEKTUS IPO DAN IMPLIKASINYA TERHADAP REAKSI INVESTOR DI INDONESIA - Indra Lila Kusuma (InFestasi, 2010)
The purpose of this research is to know and to analyze the effect of firm characteristic (Industry type, firm size and age) on intellectual capital information disclosure in IPO prospectuses, and also to know and to analize it’s implication on investor reaction in Indonesia. This research takes 61 companies from all stock exchange listing at The Indonesian Stock Exchange from 2003-2007. The selection of sample is done by using sensus method. The checklist is  used as the research supporting instrument for the documentation of the data which is  taken from Indonesian Capital Market Directory  and IPO prospectuses from all stock exchange listing at the Indonesian Stock Exchange from 2003 until 2007.  Data analysis to test the hypothesis is  multiple regression analysis by exercising software SPSS 15.   The results indicate that,  industry type and firm size have significan effect toward intellectual capital information disclosure, but age of the firm has no significan effect toward intellectual capital information disclosure. Partially, the variables influence is still pertained low seen from still the low of score total value obtained overall of sample if it is compared to maximum of obtainable score.Finally, this research also show that intellectual capital information disclosure on IPO prospectuses from all stock exchange listing at the Indonesian Stock Exchange from 2003-2007 has no effect to investor reaction in Indonesia.